STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA PENINGKATAN COMPETIFIVE ADVANTAGE - NURCAHYO DARMAWAN, ARI; YUSWANTO NUGROHO, ARIEF (STIEKOP MALANG PRESS, 2025)
Purpose – The strategic development of human resources is crucial for enhancing competitive advantage. By focusing on targeted training, skill development, and talent management, organizations can cultivate a workforce capable of driving innovation, improving efficiency, and effectively responding to dynamic market demands. This investment in human capital translates to a sustainable competitive edge through a more skilled, engaged, and adaptable workforce. Design/methodology/approach – This study employs a qualitative approach to investigate human resource development (HRD) strategies that aim to enhance competitive advantage. Data will be gathered through in-depth interviews and document analysis to explore existing HRD practices and identify potential areas for improvement within the organization. The findings will inform the development of a strategic HRD framework designed to foster a more competitive workforce. Findings – The human resource development strategy outlined demonstrably enhances competitive advantage. Findings indicate a clear correlation between targeted training programs, performance management systems, and increased employee engagement with improved organizational performance metrics. Specifically, investments in leadership development and skills-based training have resulted in measurable improvements in productivity, innovation, and customer satisfaction. This suggests that a strategic alignment of HR practices with business goals contributes significantly to achieving sustainable competitive advantage. Research limitations/implications – This study's findings regarding human resource development strategies and competitive advantage are limited by its specific context and potential for generalization to other industries or regions. Future research should explore longitudinal data to assess the long-term impact of these strategies and consider the moderating effects of organizational culture and technology adoption. The implications suggest a need for organizations to tailor HRD initiatives to their unique competitive landscape, emphasizing skills development aligned with strategic goals to achieve a sustainable advantage. Originality/value – Developing human resources strategically is crucial for fostering originality and creating value within an organization. By investing in training, skill development, and innovation programs, companies can cultivate a workforce capable of generating novel ideas and enhancing competitive advantage in the marketplace. This strategic approach ensures that human capital contributes significantly to unique solutions, improved processes, and ultimately, sustainable growth.